Chronic thromboembolic pulmonary hypertension in Australia and New Zealand: An analysis of the PHSANZ registry. Issue 12 (5th October 2021) - Kearney, Katherine; Gold, Joshua; Corrigan, Carolyn; Dhital, Kumud; Boshell, David; Haydock, David; McGiffin, David; Wilson, Michael; Collins, Nicholas; Cordina, Rachael; Dwyer, Nathan; Feenstra, John; et al.
Abstract: Background and objective: Chronic thromboembolic pulmonary hypertension (CTEPH) is a serious condition occurring in 2%–4% of patients after acute pulmonary embolism. Pulmonary endarterectomy (PEA) is a potential cure for technically operable disease. The epidemiology and long‐term outcomes of CTEPH have not been previously described in Australia and New Zealand. Methods: Data were extracted from the Pulmonary Hypertension Society of Australia and New Zealand (PHSANZ) registry for patients diagnosed with CTEPH between January 2004 and March 2020. Baseline characteristics, treatment strategies, outcome data and long‐term survival are reported. Results: A total of 386 patients were included with 146 (37.8%) undergoing PEA and 240 (62.2%) in the non‐PEA group. PEA patients were younger (55 ± 16 vs. 62 ± 16 years, p < 0.001) with higher baseline 6‐min walk distance (6MWD; 405 ± 122 vs. 323 ± 146 m, p = 0.021), whilst both groups had similar baseline pulmonary haemodynamics. Pulmonary hypertension‐specific therapy was used in 54% of patients post‐PEA and 88% in the non‐PEA group. The 1‐, 3‐ and 5‐year survival rates were 93%, 87% and 84% for the PEA group compared to 86%, 73% and 62%, respectively, for the non‐PEA group ( p < 0.001). Multivariate survival analysis showed baseline 6MWD was an independent predictor of survival in both operated and medically managed patients. Conclusion: In this first multicentre report of CTEPH in Australia and New Zealand, long‐term survival is comparable to that in other contemporary CTEPH registries. However, PEA was only performed in a minority of CTEPH patients (37.8%) and significantly less than overseas reports. Greater awareness of PEA and improved patient access to experienced CTEPH centres are important priorities. Abstract : Chronic thromboembolic pulmonary hypertension (CTEPH) is increasingly recognized as a prevalent cause of pulmonary hypertension, potentially curable with pulmonary endarterectomy (PEA) surgery. This analysis demonstrates that Australian and New Zealand patients display similar long‐term survival outcomes as internationally reported data. Strategies for improving access for Australian and New Zealand patients to PEA are an important step for advancing treatment of CTEPH in this region.